1994
DOI: 10.1111/j.1600-0684.1994.tb00112.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular immune responses in rhesus macaques infected rectally with low dose simian immunodeficiency virus

Abstract: Monkeys infected rectally with low dose simian immunodeficiency virus (SIV) were resistant to high dose challenge with SIV. Peripheral blood mononuclear cells (PBMC) from two of four challenged monkeys were unable to support SIV replication in vitro unless cultures were depleted of CD8+ lymphocytes. Monkeys that had survived high dose rectal infection with SIV also suppressed virus replication in cultured PBMC. PBMC from uninfected monkeys supported virus replication in both unfractionated and CD8-depleted cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In addition, the SIV model shows that low doses of pathogenic virus can lead to a latent infection in monkeys. In such animals, virus replication seems to be suppressed early after infection by a virus-specific cellular immune response (Dittmer et al, 1995 b, c ;Salvato et al, 1994). This observation is supported by reports on specific T cell responses in HIV-seronegative individuals exposed to HIV (Shearer & Clerici, 1996).…”
Section: Infection Of Macaques With Immunodeficiency Virusessupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, the SIV model shows that low doses of pathogenic virus can lead to a latent infection in monkeys. In such animals, virus replication seems to be suppressed early after infection by a virus-specific cellular immune response (Dittmer et al, 1995 b, c ;Salvato et al, 1994). This observation is supported by reports on specific T cell responses in HIV-seronegative individuals exposed to HIV (Shearer & Clerici, 1996).…”
Section: Infection Of Macaques With Immunodeficiency Virusessupporting
confidence: 74%
“…It has been reported that SIV-specific Th induced by low doses of infectious SIV might confer protection against a highdose challenge (Salvato et al, 1994 ;Clerici et al, 1994). This is in line with the hypothesis that humans exposed to low doses or defective strains of HIV develop virus-specific Th and are subsequently resistant to the consequences of HIV superinfection (Clerici & Shearer, 1993).…”
Section: Conclusion Implications For Vaccination and Therapy Againstmentioning
confidence: 99%
“…Ag dose is also known to affect the Th1/Th2 phenotype of the ensuing response. Most in vivo observations show that lower and higher doses, respectively, favor the generation of Th1 and Th2 cells (5,(25)(26)(27)(28)(29)(30), although some in vitro observations are inconsistent with this conclusion (31).…”
mentioning
confidence: 72%
“…Studies of the simian AIDS models have also suggested that cell-mediated immune responses play an important role in protection against simian immunodeficiency virus infection (34). It is possible that some genetic factors including HLA haplotype may also contribute to the development of resistance to HIV-1 infection (1, 8, 9).…”
Section: Discussionmentioning
confidence: 99%